The Influence of School Management Digitalization and Principals' Professional Competence on School Quality in Public Junior High Schools in Weleri Region - Nasyrohah Herfiyanti; Widya Kusumaningsih; Nurkolis Nurkolis (Nidhomul Haq : Jurnal Manajemen Pendidikan Islam, 2025)
School quality is an important indicator in improving the quality of education and is strongly influenced by the effectiveness of school management and the professionalism of school principals. Based on the data from the 2023-2024 Education Report Card in Weleri region public junior high schools, there has been a decline in several dimensions of school quality, reflecting the suboptimal management and leadership competence of school principals. One of the causes is the weak mastery of technology and the inability of principals to identify the needs of teachers to improve student abilities. The purpose of this study is to examine the effects of digitalization of school management and principals' professional competence on school quality, both individually and in combination. The data in this study were collected through the distribution of questionnaires using a Likert scale, in accordance with the quantitative approach applied. The research sample was 119 teachers from a total population of 169 teachers in Weleri Region Public Junior High School. The analysis shows that the digitalization of school management has an effect of 76.2% on school quality, with a correlation score of 0.873. The principal's professional competence affects 75.5%, with a correlation of 0.869. Simultaneously, the two variables had a 79.9% effect on school quality, with a correlation of 0.864. The findings confirm that digitalization and leadership professionalism are crucial in improving education quality. The implications of the results of this study are expected to serve as a basis for policy makers and school principals in strengthening digital management and professional development.